Shift of the tradition of "Menyama Braya" in Balinese traditional weddings at Taman Prakerti Bhuana Wedding Organizer - Ratih Wahyuni, Dewa Ayu (SABA: Journal of Tourism Research, 2024)
The development of the era that has shifted to the modern era has caused a phenomenon of change and a shift in the order of life patterns in Balinese society, especially in the field of implementation of the current wedding procession. This study aims to find out the procedures for traditional Balinese weddings and the shift in the tradition of meyama braya in Balinese traditional weddings at the Taman Prakerti Bhuana wedding organizer. This study uses a qualitative descriptive research method using Taman Prakerti Bhuana as a research subject. Data collection techniques are carried out by observation, interviews, and documentation. The results of this study indicate that Balinese weddings that use the services of wedding organizers are still held in two places, namely at home with processions of memadik, nunas tirta, and mepejati while those which are carried out in Prakerti Bhuana Park are mekalan-kalan/natab banten beten and mewidhi-widana/ natab banten beduur. All procedures are still carried out in accordance with the village of Kala Patra (traditional village rules), it's just that there has been a shift in the application of the Menyama braya tradition to several core wedding processions because it has been prepared and arranged by the wedding organizer Taman Prakerti Bhuana. The conclusion of this study is that the implementation of the Balinese traditional wedding ceremony cannot be fully carried out by the wedding organizer, but some of the processes still involve the same role. The unification of tradition with modernization is currently developing to save more costs, time and energy but does not eliminate Balinese cultural and traditional values.